Gratitude as a longitudinal mediator between social support and mental wellbeing - Akyil, Yusuf; Okur, Sinan; Erdinc, Beste; Satici, Seydi Ahmet (ELSEVIER, 2025)
Individuals derive significant advantages from the social connections they establish throughout their lives, along with the emotions of gratitude they encounter. The correlation among social support, gratitude, and wellbeing has been examined in cross-sectional studies, yet not in longitudinal research. This study aims to examine the longitudinal mediation of gratitude in the relationship between social support and mental wellbeing, addressing the identified deficiency. To overcome the limitations of mediation analysis in cross-sectional studies, the autoregressive analysis of the cross-lagged panel model in the two-wave longitudinal design was used to test the mediation of gratitude in the relationship between social support and wellbeing in the current study. Data for this model were collected at two three-month intervals. The participants of the study consisted of 233 Turkish adults. The research indicated that gratitude served as a longitudinal mediator in the association between social support and mental wellbeing. This indicates that gratitude is not simply a transient emotion but a consistent psychological characteristic that may connect interpersonal resources with enduring mental wellbeing. The importance of gratitude derived from social support for optimal mental health was underscored. These findings enhance the existing literature that underscores the enduring psychological advantages of fostering gratitude among socially connected individuals. Therefore, it demonstrates the importance of including exercises that increase gratitude and social support techniques in the framework and content of mental health interventions.
Keywords: Social support; gratitude; mental wellbeing; longitudinal study; RESILIENCE; MODERATOR; HAPPINESS; BENEFITS; STRESS; ROLES; Psychology